2007
DOI: 10.1080/10916460600695389
|View full text |Cite
|
Sign up to set email alerts
|

A Process for the Preparation of Emulsified Wax

Abstract: With the use of petroleum wax and oxidized petroleum wax as raw material and by appraising and screening emulsifier, the effects on stability of emulsifying wax such as emulsifier type, quantity, stirring speed, emulsifying time, and emulsifying temperature are discussed. The experiment results show that the mass ratio of petroleum wax and oxidized petroleum wax is 15-25%; the mass ratio of mixed emulsifier CC is 7-8%; and the best emulsifying process conditions are an emulsifying temperature of 90 ı C, an emu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…On Literature particle size phase separation 1 [24] viscosity of continuous phase particle size distribution 1 [25,26] viscosity of continuous phase phase separation 1 [27] HLB value viscosity of continuous phase 1 -HLB value particle size distribution 1 [28][29][30][31][32] HLB value phase separation 1 [33] emulsifier system viscosity of continuous phase 1 emulsifier system particle size distribution 1 [34,35] emulsifier system phase separation 1 [36] HLB value change in particle size distribution over storage time 1 [24,36,37] stirring intensity, time, and speed particle size [35,38,39] mixing temperature particle size [35,38,39] phase concentration particle size [20,30,35,[39][40][41][42] surfactant concentration particle size [30,33,35,36,38,43] aggregation state of the disperse phase particle size [44,45] phase concentration phase separation [46] 1 : Also examined in this study.…”
Section: Effect Of Parametersmentioning
confidence: 99%
See 3 more Smart Citations
“…On Literature particle size phase separation 1 [24] viscosity of continuous phase particle size distribution 1 [25,26] viscosity of continuous phase phase separation 1 [27] HLB value viscosity of continuous phase 1 -HLB value particle size distribution 1 [28][29][30][31][32] HLB value phase separation 1 [33] emulsifier system viscosity of continuous phase 1 emulsifier system particle size distribution 1 [34,35] emulsifier system phase separation 1 [36] HLB value change in particle size distribution over storage time 1 [24,36,37] stirring intensity, time, and speed particle size [35,38,39] mixing temperature particle size [35,38,39] phase concentration particle size [20,30,35,[39][40][41][42] surfactant concentration particle size [30,33,35,36,38,43] aggregation state of the disperse phase particle size [44,45] phase concentration phase separation [46] 1 : Also examined in this study.…”
Section: Effect Of Parametersmentioning
confidence: 99%
“…Griffin [29] has reported that the surfactant is the most effective when the HLB values for the surfactant and dispersed phase are the same. Hou et al [38] suggested that to first identify the most suitable HLB value, the HLB value must be varied via the blending of surfactants, as blends typically work better than single surfactants [25]. Next, the most appropriate chemical structure should be defined by maintaining a constant HLB value, albeit by varying the surfactant type.…”
Section: Short Time Stability: Effect Of Surfactantsmentioning
confidence: 99%
See 2 more Smart Citations
“…Many industrial processes will emit acidic gases containing H 2 S, such as petroleum refinery, chemical engineering, metallurgy, low-temperature coal-coking, and natural gas mining. With strong toxicity and corrosivity, H 2 S is one of the chief sources of air pollution (Hou et al, 2007). Therefore, the clean air acts of many countries demand the desulfurization of gaseous fuels to minimize the release of sulfur dioxide into the ambient air.…”
Section: Introductionmentioning
confidence: 99%